ANOMALOUS STRAIN GENERATION MECHANISM BEFORE THE MARCH 2, 1992, KAMCHATKAN EARTHQUAKE - Kuzmin Yu.O.; Churikov V.A. (My University, 1999)
Precision leveling was conducted during 3 years on a local line in a seismic fault zone in Kamchatka. The results were examined to find relations between deformation and seismicity. Superintensive vertical movements were identified in active fault zones, intersecting the leveling line, associated with the preparation of a large earthquake (M = 7.1, March 2, 1992) during the period of observation.